FORMING ENGLISH LISTENING COMPETENCE OF FIRST-YEAR STUDENTS - THE FUTURE TEACHERS OF ENGLISH - Ірина Левчик (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
Based on the analysis of psychological characteristics of first-year students (the dominance of teaching and professional activities, shift to the inner self-control and an increase in need for achievement, a high level of cognitive motivation, improvement of theoretical thinking, a tendency to individual activity, reflection, a conscious learning approach) the following peculiarities of forming English learning competence of first-year students have been outlined in the article: introduction of propaedeutic stage in order to form students' listening mechanisms and eliminate the gaps in skills; focusing on the specifics of their future professional occupation which is reflected in the themes of teaching materials and tasks to them; developing students' autonomy by enhancing their individual activity; forming students' listening strategies (training and communicative) on two stages - learning strategies and training them in use. The criteria for selection of audio texts and video and sound recording that should be used in teaching listening to first-year students have been determined.